2018
DOI: 10.1177/1744806918793229
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ2/3/5 channels in dorsal root ganglion neurons can be therapeutic targets of neuropathic pain in diabetic rats

Abstract: BackgroundDiabetic neuropathic pain is poorly controlled by analgesics, and the precise molecular mechanisms underlying hyperalgesia remain unclear. The KCNQ2/3/5 channels expressed in dorsal root ganglion neurons are important in pain transmission. The expression and activity of KCNQ2/3/5 channels in dorsal root ganglion neurons in rats with diabetic neuropathic pain were investigated in this study.MethodsThe mRNA levels of KCNQ2/3/5 channels were analyzed by real-time polymerase chain reaction. The protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
2
10
2
Order By: Relevance
“…Our findings that retigabine reduced mechanical hypersensitivity in STZ-diabetic are in line with these findings. In contrast, however, our results show that retigabine given at higher doses (15 mg/kg and 7.5 mg/kg) than that (5 mg/kg) used by these investigators [60] had no effect on heat hypersensitivity in STZ-diabetic rats. The reason for this apparent discrepancy might be due to a difference in the rat strain (Sprague Dawley in the present study versus Wistar in their study).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our findings that retigabine reduced mechanical hypersensitivity in STZ-diabetic are in line with these findings. In contrast, however, our results show that retigabine given at higher doses (15 mg/kg and 7.5 mg/kg) than that (5 mg/kg) used by these investigators [60] had no effect on heat hypersensitivity in STZ-diabetic rats. The reason for this apparent discrepancy might be due to a difference in the rat strain (Sprague Dawley in the present study versus Wistar in their study).…”
Section: Discussioncontrasting
confidence: 95%
“…Indeed, retigabine has been shown to display analgesic efficacy in multiple animal pain models including models of temporomandibular joint pain [52], visceral pain [53], inflammatory and nerve injury-induced PNP [16,44,54,55], spinal cord injury [56]; trigeminal neuropathy [57], bone cancer pain [58] and chemotherapy-induced PNP [59]. However, as far as we know, there has been only one study showing that retigabine attenuated both mechanical and heat hypersensitivity in STZ rats [60]. Our findings that retigabine reduced mechanical hypersensitivity in STZ-diabetic are in line with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of downregulation of K v 7.5 channel protein expression in small DRG neurons are partly consistent with those of [20] who also found significant decreases in the expression of K v 7.2, K v 7.3 and K v 7.5 channels at both mRNA and protein levels in STZ rats. K v 7.5 expression was also found to be down-regulated in DRG neurons following sciatic nerve axotomy [17].…”
Section: Discussionsupporting
confidence: 92%
“…However, other studies reported no change (or even a transient increase) in the expression of the K v 7.2, K v 7.3 or K v 7.5 channel proteins in DRG neurons following spinal nerve injury (see [15]. As far as we know, only one recent study examined expression of these subunits in DRG neurons in the rat STZ model of DPNP and found significant decreases in K v 7.2, Kv7.3 and Kv7.5 at both mRNA and protein levels [20]. Thus, further studies are required to unravel the apparent discrepancies between the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing KV7 currents exerts analgesic effects since hyperpolarizing the resting membrane potential of nociceptors decreases neuronal excitability [220,221]. Similarly, inhibiting KV7 currents is proalgesic since concomitant depolarization of the resting membrane potential enhances neuronal firing [222,223].…”
Section: Ion Channels As Targets Of Gpcr Signaling In Peripheral Nmentioning
confidence: 99%